Latent Membrane Protein 1 of Epstein–Barr Virus Promotes RIG-I Degradation Mediated by Proteasome Pathway - Xu, Chongfeng; Sun, Lei; Liu, Wenjun; Duan, Ziyuan (Frontiers in Immunology, 2018)
RIG-I signaling is critical to host innate immune response against RNA virus infection, and also can be activated against many kinds of cancer. Oncogene LMP1 of Epstein-Barr virus contributes to various tumors progress. In this study, we have provided strong evidence that LMP1 inhibits Sendai virus mediated type I interferon production and down regulates RIG-I signaling pathway by promotion RIG-I degradation dependent on proteasome. Nineteen kinds of E3 ligase are identified by IP-MS as LMP1 interactors, they are candidate E3s which are recruited by LMP1 to mediate RIG-I degradation. CHIP is among these E3s, which has been reported to lead RIG-I degradation. Notably, we find C666-1, an EBV positive NPC cell line, expresses low level of RIG-I, even treated with IFN-α, RIG-I expression could not be induced. This evidence indicates that EBV employs a unique strategy to evade RIG-I mediated immune responses.